Critical illustration and subversive narratives in social graphic design (Revista de Ensino em Artes, Moda e Design, 2020)
The research objective of this article is in the theoretical articulation on how the graphicdesigner can use his technical and artistic skills in favor of social causes and reflections. Forthis, critical illustration was adopted as an object of study. Initially the theoretical discussionswere oriented to the concepts that contribute, exemplify and justify how the criticism can bemade and directed to the current contemporary society. Subsequently, four illustrators fromdifferent countries were chosen so that it was possible to demonstrate how their work corroboratesthe understanding of how graphic design can not only be a professional activity thatcontributes to a company’s marketing objectives, but can also be an instrument that instigatesthe questioning and social change through the construction of a critical look.
Keywords: critical ilustration; social graphic desing; critical look